Urban solid waste management: issues and challenges of sustainability - Ghosh, Sudipto; Bhandari, Amit (Gurgaon: Palmview Publishing, 2021)
Waste management considered the most complex issue in urban areas, and it is associated with a variety of complex socioeconomic and environmental issues. Rapid urbanization, change in lifestyles and rise in population has resulted in the generation of huge quantities of solid waste. The waste management system remains primitive and has failed to evolve with the demands of the rapidly changing situation. The quantity of waste generated is much higher than the quantity collected, transported and disposed of, leading to the piling up of uncollected waste in streets, public places and drains. The unsanitary methods adopted for the disposal of municipal solid wastes pose a serious health concern. The technologies that have been attempted in India run into rough terrain, failed to bring desired environmental and public heath benefits. This book is comprised of articles highlighting the issues relating to problems in managing urban waste, sustainability in waste management practices and generating wealth from waste contributed by eminent scholars in this field.
Urban waste management in India: a political economy perspective -- Municipal solid waste management in India: challenges and prospects -- Assessment of urban solid waste management in India -- Risk assessment of biomedical wastes generated in hospitals of Chandigarh and Shimla, India -- Status of WEEE in Pune City(India) and the awareness of residents towards health and sustainability of e-waste management -- A study on issues and challenges in managing e-waste in India -- A hazard ranking system for landfill rehabilitation in India -- Understanding the waste generation scenario in Mainpat - a prolific ecotourism hub of Chhattisgarh, India -- Waste management and sustainability: supply chain perspective -- Effective use of bio-oil obtained by Pyrolysis of municipal solid waste, in flexible pavement -- Smart micro-grid technology; a case study at IIEST, Shibpur, India -- Breakthrough from the technological challenges towards recycling of municipality solid waste -- Breakthrough from the technological challenges towards recycling of municipality solid waste
Includes bibliography
Keywords: Solid Waste Management